Women of the revolution and a politics of care: A gendered intersectional approach on an initiative to address socioenvironmental problems in a marginalized community in southern Brazil - Renata Guimar\~aes Reynaldo; Kamila Pope; Juliano Borba; Stefan Sieber; Michelle Bonatti (Gender, Work & Organization, 2023)
The Buckets Revolution is a local non-governmental organization arisen from an initiative implemented in a favela, a marginalized community in the South of Brazil, led and conducted by its women to resist their condition of intersected subordinations and address the socioenvironmental problems caused by the lack of public care. Based on the understanding that women of the Buckets Revolution developed a particular politics of care, this study investigates the configuration of the complex relations between their political practice and the responsibility for care—understood as a core element of women's intersected subordination, and simultaneously, a central value for a new and revolutionary politics of care. From a qualitative approach, the case study is based on an intersectional feminist theoretical framework, epistemology, and methodological design, necessary for the analysis of gender in the South, where its imbrications with race, class, and nation compose a complex, diverse, and unequal scenario. In that sense, the women of the Buckets Revolution, by occupying a social place where these axes of subordination intersect more intensely, offer a “vantage point” to make more visible the processes of domination and resistance on both national and global levels—that is, both in Brazilian society and in an otherwise increasingly interdependent world shaped by neoliberal globalization. The gendered intersectional outline is conducted through the combination of data collection techniques, including participant observation, focus group discussions, semi-structured interviews, and bibliographical research. The results show that, with their revolutionary politics of care, the women of the Buckets Revolution built a contextualized, horizontal, and bottom-up care-based counter-hegemonic alternative to address the socioenvironmental problems that resulted from intersected subordinations in the Brazilian context, and more broadly, in the contemporary neoliberal global order.
Keywords: 300; gender; race and class intersections; marginalized community; politics of care; socioenvironmental initiative